Construction of Assessment Models to Enhance Students’ Multiple Intelligence in Islamic Boarding Schools - Qodir, Abdul; Fauzi, Ahmad; Dakir (International Journal of Psychosocial Rehabilitation, 2020)
This research, praxis aims to explain the construction of assessment models in Islam, by transmitting all the values of Islamic teachings that originate from the Qur’an and al-Hadith, such as; promote honesty, objectivity, including shidiq, amanah, tabligh and fatonah attitudes; openness; justice, transparency, accountability and sustainability (istiqomah). Internalization of these values, becomes core beliefs and values in building a new paradigm (shifting paradigm) in the assessment of Islamic education, which is more praxis and becomes one of the proto-types of ideal assessment. The construction of the assessment model above is a manifestation of the weakness of the quality of Islamic education today, as a result of the assessment activities that are formal, spontaneous and insedental, and have not even been able to carry out substantial evaluation activities. Therefore, as an effort to provide a holistic understanding, this study uses a qualitative approach and is descriptive in nature, inductive descriptive with data collection techniques through structured interviews, semistructured intervie, participant observation, so as to produce grounded theory. In this context, the assessment model is expected to provide practical solutions, and as a new breakthrough in building the quality of graduates, who have intellectual intelligence (aqliyah), emotional and spiritual (qolbiyah) and skills (amaliyah), or better known as (multiple intelligence), so that the existence of Islamic education is truly a superior educational institution (central for excellence).